2020
DOI: 10.3389/fgene.2020.00790
|View full text |Cite
|
Sign up to set email alerts
|

HuD Binds to and Regulates Circular RNAs Derived From Neuronal Development- and Synaptic Plasticity-Associated Genes

Abstract: The RNA-binding protein (RBP) HuD is involved in neuronal differentiation, regeneration, synaptic plasticity and learning and memory. RBPs not only bind to mRNAs but also interact with several types of RNAs including circular RNAs (circRNAs), a class of non-coding RNAs generated by pre-mRNA back-splicing. This study explored whether HuD could regulate the expression of neuronal circRNAs. HuD controls target RNA’s fate by binding to Adenylate-Uridylate Rich Elements (AREs). Using bioinformatics analyses, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 75 publications
5
30
0
Order By: Relevance
“…Recently, using bioinformatical prediction, it has been shown that neuronal HuD protein (ELAVL4) contained AU-rich elements that were attractive for hundreds of mice brain-expressed circRNAs. RNA immunoprecipitation confirmed this finding and showed that approximately 600 mice brain-expressed circRNAs could interact with HuD [112]; moreover, 226 of them originated from the previously described circHomer1a gene [28].…”
Section: The Role Of Rna Binding Proteins (Rbps) In Schizophrenia: Circular Rnas As Sponges For Rbpssupporting
confidence: 53%
“…Recently, using bioinformatical prediction, it has been shown that neuronal HuD protein (ELAVL4) contained AU-rich elements that were attractive for hundreds of mice brain-expressed circRNAs. RNA immunoprecipitation confirmed this finding and showed that approximately 600 mice brain-expressed circRNAs could interact with HuD [112]; moreover, 226 of them originated from the previously described circHomer1a gene [28].…”
Section: The Role Of Rna Binding Proteins (Rbps) In Schizophrenia: Circular Rnas As Sponges For Rbpssupporting
confidence: 53%
“…[129] is reduced in the frontal cortex of ALS patients [129] TAF15 miR-17-92 CDKN1A/p21 regulates miRNA biogenesis to decrease genes related to cell proliferation [132] is reduced in an SOD1 G93A mouse model [133] hnRNP A1 miR-590-3p n.d. is cooperatively regulated in neuronal maintenance ? [135] is increased in the blood cells of FTD patients [135] hnRNP H miR-663a CDK4, CDK6 is cooperatively regulated in cellular senescence by targeting genes related to the cell cycle [137] is increased in the blood cells of ALS patients [138] RALY miR-483 ATP5I, ATP5G1, ATP5G3, CYC1 regulates miRNA biogenesis to decrease genes related to mitochondrial metabolism [140] n.d. miR-676 miR-877 RBM17 miR-150-5p VEGF-A is cooperatively regulated in genes related to growth factors [143] is reduced in the CSF of ALS patients [145] HuD miR-125a-5p CAMSAP3 cooperatively regulates circRNA in aging by targeting genes related to neuronal polarization [148] is reduced in aging mice [147] Matrin-3 miR-138-5p n.d.…”
Section: Interplay Between Rna-binding Proteins and Micrornas In Neurodegenerative Diseasementioning
confidence: 99%
“…HuD has been reported to regulate ALS-associated SOD1 expression during oxidative stress in differentiated neuroblastoma cells and the sporadic ALS motor cortex [ 146 ]. HuD binds to and regulates circular RNAs derived from genes regulating neuronal development and synaptic plasticity and may act as a sponge for the miRNAs such as miR-125a-5p, which has previously been reported to be associated with aging [ 147 , 148 ]. Matrin-3 was recently found to be strongly linked to the pathogenesis of ALS [ 149 , 150 , 151 ] and has been shown to regulate processing of the synaptic miR-138-5p [ 152 ] ( Table 2 ).…”
Section: Interplay Between Rna-binding Proteins and Micrornas In Neurodegenerative Diseasementioning
confidence: 99%
“…HuD–associated mRNAs have been analyzed by ribonucleoprotein immunoprecipitation (RIP) followed by microarray in the brains of transgenic mice [ 58 ], and also by CRAC (crosslinking and analysis of cDNA) in motor neuron cells expressing His–HA–HuD [ 52 ]. Recently, a series of HuD–associating circular RNAs (circRNAs) from HuD transgenic mice were identified by RIP analysis followed by circRNA arrays [ 60 ]. These analyses revealed that HuD interacts with a variety of mRNAs as well as non–coding RNAs, via their ARE regions and provided useful information concerning the roles of HuD in RNA regulation.…”
Section: Regulation Of Rna Metabolism By Hudmentioning
confidence: 99%
“…In addition to targets found in neuronal tissues, HuD promotes stabilization of target mRNAs also expressed in other tissues, such as p21 [ 83 ], Ca 2+ /Calmodulin–dependent protein kinase II α ( CaMKII α) [ 84 ], and musashi 1 ( MSI1 ) [ 85 ]. Additionally, an interesting study recently demonstrated that circRNAs, such as cirHomer1a , could be molecular targets of HuD [ 60 , 86 ].…”
Section: Regulation Of Rna Metabolism By Hudmentioning
confidence: 99%